Precipitation on grain boundaries in Al-Mg-Si alloys: The role of grain boundary misorientation. (1st April 2022) - Zhang, Zhijun; Parson, N.C.; Poole, W.J.
Abstract: The application of Al-Mg-Si alloys is growing in fracture critical applications such as transportation. The formation of grain boundary precipitates during cooling after solution treatment is an important factor in controlling low energy intergranular fracture modes. A systematic study was conducted on the effects of grain boundary misorientation and cooling rate (between 3 and 1000 °C/s) on the size and density of grain boundary precipitates before and after artificial ageing. It was found that precipitates on high angle grain boundaries were ≈3 times larger than those formed on low angle boundaries. The grain boundary precipitate size decreased by a factor of 3 when the cooling rate increased from 3 to 80 °C/s with no precipitates observed at 1000 °C/s. However, even for a cooling rate of 1000 °C/s, grain boundary precipitation was observed during subsequent artificial ageing. The effects of grain boundary misorientation and cooling rate were rationalized by enhanced diffusion at grain boundaries. Abstract : Image, graphical abstract